أعراف المسلمين في الخطبة والنكاح والطلاق بمقاطعة خنان الصينية : دراسة تحليلية نقدية - هي لين، لي (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This study addresses the customs of family engagement, marriage and divorce in Henan Province in the People's Republic of China. It aims at analysing and dividing the customs of engagement, marriage and divorce by the provisions of Islamic law on the family. This study consists of five chapters, the first chapter contains the introduction; the second chapter describes the customs of engagement among Henan Hui Muslims; the third chapter indicates the customs of marriage between Muslims in Henan; the fourth chapter discusses the customs of divorce between Henan Hui Muslims while the last chapter describes the result of the field study. The methodology of this study used the induction approach in its analysis. It concludes that there are major custom differences from the Islamic law relating to engagement, for example “the idea of freedom of acquaintance between engaged couples without restrictions” and the "custom allowing engaged couples to go out together without being accompanied by a parent or guardian.” If they dissolute the engagement, there is no need to return the dowry. In the marriage customs, e.g. for a non- Muslim to marry a Muslim, he or she has to embrace Islam before the wedding ceremony. Also it is a ritual to present seeds at the solemnization stage to seek blessings for the married couple's future. About the divorce issue, for instance, Henan Hui Muslims frequently utter the words of "divorce" (li hun) without following the Islamic law. Also, there is no period of waiting (iddah) after divorce. This study aims to help Chinese Muslims realize the eroneous traditions which have to be corrected or be rid off .